Pengaruh Fasilitas dan Lingkungan Kerja Terhadap Kepuasan Kerja Pegawai pada Kantor Camat Kecamatan Bajubang - Budi Darma; Kasiyati Wulansari (CITRA EKONOMI, 2022)
This study discusses the effect of work facilities and work environment on job satisfaction of the employees of the District Head Office of Bajubang. The variables of work facilities and environment act as independent variables, while the variable of job satisfaction acts as the dependent variable. The analytical tool used in this research is Multiple Linear Regression. This is because of the two independent variables used in this study. Then to test the hypothesis used t test and F test, as well as the coefficient of determination to determine the magnitude of the contribution of the variable work facilities and work environment to job satisfaction. The conclusion of this study is that based on the results of the t-test, the work facilities variable does not have a partial effect on job satisfaction at the Bajubang District Head Office, while the work environment variable has a partial influence on job satisfaction at the Bajubang District Head Office. In the results of the F test, the variables of work facilities and work environment have a joint influence on job satisfaction. From the results of the coefficient of determination, the Adjusted R Square value is 0.65. This means that the variables of work facilities and work environment affect job satisfaction by 65%. While 35% that affect job satisfaction is influenced by other variables that are not discussed in this study.